The 13th Malaysian general election: uncertainties and expectations - Moniruzzaman, Md. (IIUM Press, 2013)

(untitled)
Malaysia held its 13th general election on May 5, 2013 which was a contest between two coalitions, the ruling Barisan Nasional (BN) and the opposition Pakatan Rakyat (PR). The latter's expectations for an outright win did not materialise. The election results have shown a rather status quo with minor losses and gains for the two coalitions. This study analysed the 13th election and found a number of noticeable trends. The Chinese voters have voted overwhelmingly for the opposition. The political culture of Malaysia is also shifting toward more participatory type with increased social and economic mobility. The days of one-party dominance in Malaysia are apparently over. The electoral politics in Malaysia might become more polarised along ethnic lines which may require reshuffling of its coalition framework and design.